Comparation of Trading Volume Activity and Abnormal Return Before and After Boycott, Divestment and Sanction Movement - Munawarah, Munawarah; Muslimin, Muslimin; Kasim, Muhammad Yunus; Zainuddin, Fatilina; Kadang, Juliana (International Journal of Social Science and Business, 2025)
The boycott, divestment, and sanctions (BDS) movement targeting Israeli‑affiliated firms has gained considerable global attention, yet its impact on Indonesian capital markets remains underexplored. This study therefore investigates whether the announcement of trading suspension in response to BDS actions is associated with significant changes in mean abnormal returns and trading volume activity for affected stocks. Employing an event‑study framework, we calculate abnormal returns using the market model and measure trading volume activity as the ratio of daily volume to its historical average over a 21‑day window (ten days before through ten days after the event date). Our sample comprises Israeli‑linked firms listed on the Indonesia Stock Exchange whose trading was halted due to BDS‑related developments. Rigorous statistical tests reveal that mean abnormal returns are significantly different both in the pre‑event and post‑event periods, indicating that investors adjust their valuation prior to as well as following the suspension. Likewise, a paired‑samples t‑test of trading volume activity demonstrates a statistically significant increase in turnover immediately before and after the event, suggesting heightened trading interest surrounding the BDS announcement. These findings underscore that non‑fundamental political actions can elicit measurable market reactions in Indonesia, with implications for portfolio managers, regulators, and policymakers seeking to understand how socio‑political events influence market dynamics.